2016
DOI: 10.1111/bph.13506
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐inducible gene‐6 partly mediates the inhibitory effects of prenatal dexamethasone exposure on endochondral ossification in long bones of fetal rats

Abstract: BACKGROUND AND PURPOSEPrenatal exposure to dexamethasone slows down fetal linear growth and bone mineralization but the regulatory mechanism remains unknown. Here we assessed how dexamethasone regulates bone development in the fetus. EXPERIMENTAL APPROACHDexamethasone (1 mg·kg À1 ·day À1 ) was injected subcutaneously every morning in pregnant rats from gestational day (GD)9 to GD20. Fetal femurs and tibias were harvested at GD20 for histological and gene expression analysis. Femurs of 12-week-old female offspr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Our recent work and work from other groups demonstrated that synthetic glucocorticoid dexamethasone can up-regulate the expression of OPG (Swanson et al, 2006;Zhang et al, 2016), and prenatal dexamethasone exposure can retard bone development in fetus, which is closely associated with low bone mass in later life of offspring (Cheng et al, 2014). Consistent with this, our present study showed that CORT but not ethanol activated the mRNA expression of OPG in chondrocytes without affecting the expression of RANKL, and mifepristone block the activating effect of CORT on OPG expression.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Our recent work and work from other groups demonstrated that synthetic glucocorticoid dexamethasone can up-regulate the expression of OPG (Swanson et al, 2006;Zhang et al, 2016), and prenatal dexamethasone exposure can retard bone development in fetus, which is closely associated with low bone mass in later life of offspring (Cheng et al, 2014). Consistent with this, our present study showed that CORT but not ethanol activated the mRNA expression of OPG in chondrocytes without affecting the expression of RANKL, and mifepristone block the activating effect of CORT on OPG expression.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Our previous work demonstrated that continuous PDE during GD 9-20 retards long bone development in fetal rats and leads to low bone mass in adult rat offspring [7], and further delineated that PDE at dose higher than 0.8 mg/kg/day during GD 12-14 developed severe retardation of long bone development in fetal mice [6]. In the present study, the data clearly indicate that PDE at 1.2 mg/kg/day during GD 12-14 induces low bone mass in 12-week-old mice offspring.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical trial data show that lower birth weight is associated with lower peak bone mass in adult offspring [4,5]. Evidence from experimental animal models by our group and others demonstrate that prenatal dexamethasone exposure (PDE) impairs long bone development in fetal animals [6][7][8][9], reduces bone mass in adult offspring [7,10]. These data imply that developmental overexposure to glucocorticoid alters bone programming and results in less bone mass in offspring.…”
Section: Introductionmentioning
confidence: 87%
“…Our previous work demonstrated that continuous PDE during GD 9-20 leads to low bone mass in adult rat offspring [7], and further delineated that PDE at dose higher than 0.8 mg kg ̶ 1 day ̶ 1 during GD 12-14 developed severe retardation in bone development in new born mice [6]. In the present study, the data clearly indicate that PDE at 1.2 mg kg ̶ 1 day ̶ 1 during GD 12-14 induced low bone mass in 12-…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical trial data show that lower birth weight is associated with lower peak bone mass in adult offspring [4,5]. Evidence from experimental animal models by our group and others demonstrate that prenatal dexamethasone exposure (PDE) impairs long bone development in fetal mice and rat [6,7], reduces bone mass in adult rat offspring [7]. These data imply that developmental overexposure to glucocorticoid alters bone programming and results in less bone mass, while few studies have identified the cellular targets of prenatal glucocorticoid exposure in the developing bone.…”
Section: Introductionmentioning
confidence: 99%